PERAN MANAJEMEN PENGETAHUAN DALAM HUBUNGAN ANTARA INOVASI ORGANISASI DAN PRAKTIK PRAKTIK MANAJEMEN SUMBER DAYA MANUSIA - Mulyadi; Sudianto; Wawan Fajar (LPPM Universitas Ibnu Sina, 2022)
The increasingly competitive in business world requires companies to continue to innovate in order to survive in the Market Dynamics. The world economy is currently starting to shift to a knowledge-based economy in its human resource management practices, which are expected to achieve organizational innovation. Therefore, the authors are interested in discussing specifically how the role of knowledge management mediates the relationship between organizational innovation and human resource management practices.